BIOFACE: A prospective study of risk factors, cognition and biomarkers in a cohort of individuals with early‐onset mild cognitive impairment at Fundació ACE. (31st December 2021) - Antonio, Ester Esteban‐De; Pérez‐Cordón, Alba; Gil, Silvia; Cano, Amanda; Orellana, Adelina; Alegret, Montserrat; Espinosa, Ana; Alarcón‐Martín, Emilio; Valero, Sergi; Martínez, Joan; Montrreal, Laura; de Rojas, Itziar; et al.
Abstract: Background: The diagnosis of mild cognitive impairment (MCI) due to Alzheimer's disease (AD) is based on either cerebrospinal fluid (CSF) or neuroimaging biomarkers (Albert et al, 2011). Currently, several non‐invasive and cheaper blood‐based biomarkers are being investigated, including neuronal‐derived plasma exosomes (NPEs) (Winston et al, 2016). The role of neuroinflammation, oxidative stress and early vascular changes, prior to the onset of amyloidosis, has been described in the pathogenesis of AD (Iturria‐Medina et al, 2016) and vascular‐related proteins can be traced in plasma and NPEs using proteomics. However, these changes have not been studied in early onset MCI (EOMCI), that is, when symptoms begin under the age of 65 (Rossor et al, 2010). Objective: To describe the rationale, study design and baseline characteristics of the BIOFACE cohort, a two‐year prospective observational study on EOMCI conducted at Fundació ACE in Barcelona, Spain. The study goal is to characterize different clinical, neuropsychological and biomarker phenotypes and to investigate CSF and plasma proteomics as well as the role of NPEs as early biomarkers of AD. Method: Participants underwent neurological and neuropsychological batteries and multimodal biomarkers including brain MRI, APOE genotyping, plasma and NPEs, saliva, CSF, non‐invasive arterial peripheral testing, anthropometrics and neuro‐ophthalmological examinations. In the final visit, participants will undergo brain MRI, lumbar puncture and blood extraction for NPEs. Result: Ninety‐seven patients with EOMCI were recruited. Most participants were women (59.8%). Mean age at symptom onset was 57 years; mean MMSE score was 28 with a mean of 12.13 years of education. First degree and presenile family history of dementia was present in 60.8% and 15.5%, respectively. Depressive and anxiety disorders, along with vascular risk factors, were the most frequent comorbidities. Syndromic diagnoses were established: possible amnestic MCI (n=32), possible non‐amnestic MCI (n=33), probable amnestic MCI (n=16) and probable non amnestic MCI (n=16). CSF biomarkers (ATN classification): A+ (n=15), A‐T/N+ (n=13), A‐T‐N‐ (n=57). Conclusion: BIOFACE is a two‐year observational study of cognition and biomarkers that will shed light on the physiopathology and the potential utility of plasma proteomics and NPEs as non‐invasive early diagnostic and prognostic biomarkers in individuals with early onset MCI.